Aplicabilidad del Pronóstico de Variabilidad Climática Estacional: El Manejo de Riesgos en la Producción del Tomate en el sur del Estado de Florida - Norman Breuer; Clyde Fraisse; Gene McAvoy; David Letson (EDIS)
AE462, a 9-page illustrated fact sheet by Norman Breuer, Clyde Fraisse, Gene McAvoy, and David Letson, is the Spanish language version of “CIR1450/AE269 Using Seasonal Climate Variability Forecasts: Risk Management for Tomato Production in South Florida.” It describes the difference between weather and climate, suggests climate-based management options available to tomato growers, and discusses economic and risk management implications of seasonal climate variability for tomato producers and extensionists in South Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, May 2010.